2019
DOI: 10.1515/geo-2019-0007
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon Generation Potential of Chia Gara Formation in Three Selected Wells, Northern Iraq

Abstract: In this study collected samples of Chia Gara Formation in Atrush, Shaikhan and Sarsang oilfields are used to geochemical characteristics of organic matter in this formation. This determination was based on Rock-Eval pyrolysis and Biomarker analyses. The Chia Gara Formation can be considered as good to excellent source rock; it’s TOC content ranges from 1.14-8.5wt% with an average of 1.85%, 3.91%, and 6.94% in Atush-1, Mangesh-1 and Shaikhan-8 wells respectively. The samples of Chia Gara Formation contain kerog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…[19] examined the Lower Sarmord biostratigraphy in well kirkuk-109 and identified the biostratigraphic zones. In the study of [20] found that the petrophysical characteristics of Sarmord Formation in northern Iraq are made up of limestone and dolomitic limestone and have a long history of good porosity. [21] Examined the stratigraphy and nannofossi biozonation of Sarmord Formation in northern Iraq and conclude that it dates from the Late Valanginian -Barremian.…”
Section: Geological Settingmentioning
confidence: 99%
“…[19] examined the Lower Sarmord biostratigraphy in well kirkuk-109 and identified the biostratigraphic zones. In the study of [20] found that the petrophysical characteristics of Sarmord Formation in northern Iraq are made up of limestone and dolomitic limestone and have a long history of good porosity. [21] Examined the stratigraphy and nannofossi biozonation of Sarmord Formation in northern Iraq and conclude that it dates from the Late Valanginian -Barremian.…”
Section: Geological Settingmentioning
confidence: 99%